Global economic impact of the COVID-19 pandemic. Analysis from the most affected sectors - Araújo Vila, Noelia (2020)
Nowadays, The COVID-19 is a virus already known by everyone, given the pandemic situation that has been declared worldwide. This is an unprecedented health crisis in the current history, which has forced the governments of several countries to take restrictive measures regarding the business activity and mobility of citizens. The research analyses, firstly, the consequences of this world crisis on the economy, through economic indicators such as stock market values, oil price, rate of unemployment or the GDP index of countries such as Spain or the United States. Then, the study focuses on two of the most affected sectors: Tourism and trade. Through qualitative analysis by in-depth interviews, reveals how these two sectors have lived this crisis and which are their expectations.